THE ROLE OF SOCIAL MEDIA IN MODERN JOURNALISM - Burxanov Hamid Sayfutdinovich (International Journal of Literature and Language Studies, 2026)
This article analyzes the impact of social media on the development of modern journalism. In particular, the role of platforms such as Telegram, Facebook, Instagram, and YouTube in information dissemination, their importance in journalistic activities, and their influence on communication with audiences are examined. The study explores the opportunities of social media in rapid information exchange, interactivity, and multimedia content creation, while also analyzing their advantages and challenges in contemporary journalism.